Lean in agriculture : create more value with less work on the farm - Fladkjær Nielsen, Vibeke; Pejstrup, Susanne (Routledge/Productivity Press, 2018)
Responding to a recent surge in interest, this is the first book to comprehensively address how Lean thinking and tools can be implemented in agriculture. This handbook breaks down barriers, clearly showing how techniques originally developed for use in factories work just as well on farms. Expert Lean farming consultants Susanne Pejstrup and Vibeke Fladkjaer Nielsen present these methods in a clear, easy-to-read style, accessible to farmers the world over. Case studies from multiple farm types - including crops, pigs and dairy cattle - demonstrate how respect for people, continuous improvement and visual management techniques can improve resilience and profitability on the farm. Richly illustrated, Lean in Agriculture appeals not only to farmers, but to farm workers, food processing companies, veterinarians, consultants and other stakeholders in the agribusiness sector.